Performance analysis and development of OPD interconnection network using NDLC method in Boven Digoel Diskominfo Papua Province - Puspa Ira Dewi Candra Wulan; Danis Putra Perdana; Aldhi Ari Kurniawan (Compiler, 2022)
Computer network analysis is very important to help improve network performance. Many companies, including digoel boven diskominfo designed their network but not according to their business goals, so their current performance is not what they expected. Boven Digoel Diskominfo uses internet interconnection between Local Government Organizations (OPD) to manage the system. Network analysis at the Boven Diego Diskominfo is carried out using the Network Development Life Cycle (NDLC) method relying on the previous infrastructure development process which has several stages, namely analysis, design, prototype simulation, implementation, monitoring, and management. The results of this network analysis are the optimization of the core router and the optimization of the Wireless Access Point